Difference or Disappearance: The Politics of Indigenous Inclusion in the Liberal State - Macdonald, Gaynor (Anthropologica, 2022)
The effects of neo-liberal economies have meant that effective social inclusion of marginalized groups is of increasing concern, yet it is arguable that economic marginalization as well as the marginalizing of difference are increasing. This paper questions the taken-for-granted view that liberal democratic states want and are able to include. It draws on recent experiences of an Aboriginal network in Australia to argue that liberal democracies are resistant to inclusion of certain kinds and that this is most evident in circumstances where Aboriginal people appear to be making successful headway in state-initiated entrepreneurship.